Electroacupuncture Ameliorates Acute Myocardial Ischemic Injury and Long QT Interval in Mice through the α1A-Adrenergic Receptor: Electrophysiological, Morphological, and Molecular Evidence. (30th June 2022) - Zuo, Haiyan; Cui, Shuai; Wang, Kun; Wu, Xin; Zhou, Jie; Qu, Qiaoyu; Tong, Yan; Wu, Shengbing; Zhou, Meiqi
Abstract : Acute myocardial ischemia (AMI) is a condition caused by a decrease in blood flow to the heart that can sometimes predispose to acquired long QT syndrome (LQTS), thereby resulting in sudden cardiac death. Recent evidence indicates that electroacupuncture (EA) can alleviate MI injury, but its specific mechanism remains unclear. This study was aimed at investigating the efficacy of EA, which utilizes α 1A -adrenergic receptors ( α 1A -AR) in alleviating MI injury as well as the resulting LQTS. The AMI model was established by ligating the left anterior descending arteries (LAD) of both the wild-type and α 1A gene-knockout mice and treating them with EA for three consecutive days. A PowerLab 16 physiological recorder was used to collect the electrocardiogram (ECG) while the serum creatine kinase isoenzymes (CK-MB), lactate dehydrogenase (LDH), and norepinephrine (NE) levels in myocardial tissue were determined by using the enzyme-linked immunosorbent assay (ELISA) kit. Moreover, TTC staining was used to observe the myocardial ischemic area, while H&E and TUNEL staining determined the pathological morphology of the myocardium. Quantitative real-time PCR (qRT-PCR) was used to detect the α 1A mRNA, and Western blot was used to detect the specific proteins, such as α 1A, cleaved caspase-3, Gq, PLC, p-PKC α, and p-hERG. Our results showed that EA could effectively reduce elevated ST-segment, shorten the extended QT interval, and reduce the serum myocardial enzyme content and the degree of pathological injury in wild mice with MI. EA can also decrease the expression of α 1A -AR, PLC, p-PKC α, and NE content in myocardial tissues of wild mice, while those of p-hERG increased in ischemic myocardial tissue. These findings suggested that α 1A -AR is involved in the development of MI as well as LQTS. Additionally, EA treatment improves the cardiac function and ischemic long QT interval and plays an important role in reducing the hERG inhibition through the α 1A -AR-mediated Gq/PLC/PKC α pathway and myocardial apoptosis. Hence, it is suggested that α 1A -AR might become a potential target for EA in treating AMI treatment of myocardial ischemia injury and acquired long QT intervals caused by MI.